Hungarian Monitoring, 16 February 1990 . [Magyar rádiófigyelő], 1990. február 16 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - Columbian drugs conference - Situation in Tajikistan - Mitterrand-Kohl meeting - Romanian premier in talks in Paris - The new Germany - Czechoslovakia: the Moldva-gate affair Domestic Affairs: - Ministerial council in session - Election: election programs, party programs, voter endorsement forms scandal - Helsinki Committee on the ignorance of voters - Tiszagate scandal - Dunagate - Defense Ministry denies that Hungary wants to sell MIG-29 fighters to Iraq Economy: - Hungarian National Bank signs ATS 1 million share credit agreement - Relations between the Common Market and Hungary Külpolitika: - Kolumbiai kábítószer csúcstalálkozó - Tádzsikisztáni helyzetkép - Mitterrand-Kohl találkozó - A román miniszterelnök Párizsban tárgyal - Az új Németország kérdése - Csehszlovákia: Moldva-gate ügy Belpolitika: - A Minisztertanács ülése - Választás: választási műsorok, pártprogramok, kopogtatócédula botrány - A Helsinki Bizottság a választópolgárok tájékozatlanságáról - Tiszagate botrány - Dunagate-ügy - A HM cáfolja, hogy Magyarország MIG-29-s vadászrepülőket akar eladni Iraknak Gazdaság: - A Magyar Nemzeti Bank egy milliárd osztrák schillinges kötvényhitel megállapodást írt alá - Közös Piac és Magyarország kapcsolata